Unusual Anterior Neck Swelling: Cervical Spinal Cord Schwannoma - Özgiray, Erkin; Karagöz, Cihat; Bölük, Serdar; Balak, Naci (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Schwannomas are typically solitary, well-encapsulated, benign tumors running along or attached to a nerve. An intradural-extramedullary cervical spinal schwannoma, which first manifests as a swelling in the anterior neck, has not been reported to the best of our knowledge. We present the case of a 69-year-old patient complaining of a gradually worsening painful left cervical swelling for over 8 years. First, a posterior spinal midline approach was performed for the resection of the tumor and the tumor portion in the vertebral canal was totally removed. The second operation, the anterolateral approach, was planned to be executed in a second surgical session. The patient was discharged from the hospital without neurological deficits. Histopathological diagnosis was a schwannoma. The first aim of surgery is to treat neurological deficits in patients with cervical intraspinal schwannomas with/without extension into the extra-vertebral paravertebral neck regions. The surgical strategy combines the posterior midline and the anterolateral cervical approaches in the same session or at different times.
Keywords: cervical neuroma; dumbbell schwannoma; neck mass; neck swelling; spinal schwannoma